Stranger in My Own Body : Atypical Gender Identity Development and Mental Health. - Di Ceglie, Domenico (Karnac Books, 1998)
This book brings together the contemporary thinking of a number of international clinicians, researchers and professionals from different disciplines. It shows the various perspectives that can be adopted on atypical gender identity development, and its relevance to mental health in children and adolescents. It is aimed at a multidisciplinary professional readership, as well as the interested lay reader. 360 pages.